Quality as a public good: The Diamond Open Access Standard (DOAS) and its role in the Global Diamond Open Access Alliance - Rooryck, Johan; Rico Castro, Pilar; de Pablo Llorente, Virginia (Septentrio Conference Series, 2024)
The Diamond OA Standard (DOAS) sets out a comprehensive standard for Diamond Open Access (OA) journal publishing. It defines a shared understanding of quality in terms of 7 core components first outlined in the Action Plan for Diamond Open Access (Ancion et al. 2022: 4), and revised and modified by the DIAMAS project’s team: Funding; 2. Legal ownership, mission, and governance; 3. Open Science; 4. Editorial management, quality, and research integrity; 5. Technical service efficiency; 6. Visibility, communication, marketing, and impact; 7. Equity, Diversity, Inclusion, and Belonging (EDIB), multilingualism, and gender equity. DOAS sets a course towards quality improvement that all Diamond OA journals can align on via the DOAS self assessment tool. Even more importantly, it evinces the notion that the quality of academic publishing is a public good that should be acknowledged, defended, and preserved. The quality of academic publishing is the responsibility of the entire academic community: authors, editors, reviewers, and readers, requiring vigilance and a critical stance from all participants in the publishing process. DOAS was co-created in collaboration with the Diamond OA publishing community in Europe through an iterative participatory process. First, DIAMAS team members carried out an extensive analysis of 71 documents on quality standards and best practices in scholarly publishing, which revealed a global consensus on editorial quality. This analysis led to a first version of a quality standard for Diamond OA publishing, which was called EQSIP v1. This version was further refined via a gap analysis and feedback from eight focus groups involving 300 people from various European Diamond OA publishing communities, resulting in a second version, the Extensible Quality Standard in Institutional Publishing (EQSIP) v2.0 for Diamond Open Access. This version was then republished as DOAS, to underscore its relevance beyond the DIAMAS project outputs EQSIP 1.0 and 2.0. As one of the main outcomes of the DIAMAS project, DOAS will soon be discussed at the global level in the context of the EC-funded ALMASI project, forging Diamond OA collaboration in Africa, Europe, and Latin America, as well as the Global Diamond Open Access Alliance announced by UNESCO on July 2024. See this presentation in this video recording.